Epistatic and QTL × environment interaction effects on leaf area‐associated traits in maize. (December 2016) - Wei, Xiaomin; Wang, Xiaobo; Guo, Shulei; Zhou, Jinlong; Shi, Yong; Wang, Huitao; Dou, Dandan; Song, Xiaoheng; Li, Guohui; Ku, Lixia; Chen, Yanhui
Abstract: Leaves play important roles, including in photosynthesis and transpiration, during plant development. Therefore, studying the genetic mechanisms affecting leaf size may contribute to improving plant architecture through molecular design. However, the genetic mechanisms that underlie these traits remain poorly understood. In this study, quantitative trait loci (QTL) for traits related to leaf area were identified using a set of recombinant inbred lines evaluated in three environments by 1226 single nucleotide polymorphic markers. In total, 16 QTL were detected with four QTL showing effects of greater than 10%. Five of the QTL explained 46.02%, seven of the QTL explained 46.77%, and four of the QTL explained 30.03% of the phenotypic variance of leaf length, width and area, respectively. Additional epistatic effects were identified for all of the maize chromosomes, except for chromosomes 7, 8 and 9. All of the epistatic effects involved pairs of loci on different chromosomes. Thus, a complex network controlling these traits was found in maize. These results provide useful information for understanding the molecular mechanisms controlling maize leaf size.